Measuring mentalizing in youth: further validation of the reflective functioning questionnaire for youth (RFQY-13) - Martin-Gagnon, Gabriel; Fonagy, Peter; Bégin, Michaël; Normandin, Lina; Ensink, Karin (Frontiers in Psychology, 2023)
Objective This study investigated the psychometric properties, including the factor structure, validity, and reliability of the 13-item Reflective Function Questionnaire for Youth (RFQY-13), using a new scoring system. Method A community sample of 414 adolescents and a clinical sample of 83 adolescents (aged 12–21) completed the RFQY, the Borderline Personality Features Scale for Children (BPFS-C), the Beck Youth Inventories (BYI), the Child Behavior Checklist-Youth Self Report (CBCL-YSR) and the Movie for the Assessment of Social Cognition (MASC). Results Using the new scoring system, our results demonstrated configural and metric invariance, as well as adequate reliability and validity across both samples for the two-factor structure of the RFQY. The Uncertainty subscale also showed strong associations with psychopathology. Discussion The findings show that the RFQY-13, when used with the new coding system, has good psychometric properties and is a reliable measure of mentalizing for adolescents and young adults. We discuss clinical implications, limitations and future directions.